PENERAPAN MODEL PEMBELAJARAN GROUP INVESTIGATION DALAM PEMBELAJARAN MATEMATIKA PADA MATERI HIMPUNAN - Anggi Meylia Saraswati; Abdul Aziz Saefudin (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2017)
The study explain about implementation Group Investigation’s model of mathematics learning in set subject. Group Investigation’s model is cooperative learning models that requires students to be actively involved, creative, dan scientific to develop idea to solve some problems. The implementation Group Investigation’s model of mathematics learning based on teacher centered learning problem. The implementation Group Investigation’s model of mathematics learning in set subject expected to be a solution of the problem learning and the learning can go well.